Poor People's Knowledge : Promoting intellectual property in developing countries - Finger, J. Michael; Schuler, Philip (Washington, D.C. : Copublication of the World Bank and Oxford University Press, 2004)
This book is about increasing the earnings of poor people in poor countries from their innovation, knowledge, and creative skills. Case studies look at the African music industry; traditional crafts and ways to prevent counterfeit crafts designs; the activities of fair trade organizations; biopiracy and the commercialization of ethnobotanical knowledge; the use of intellectual property laws and other tools to protect traditional knowledge. It will be of interest to students and scholars of international trade and law, and to anyone with an interest in ways developing countries can find markets for cultural, intellectual, and traditional knowledge.
Includes bibliographical references and index.
rpm 08/09/16
Loans
Keywords: Intellectual property; Intellectual property (International law).; LAW -- Administrative Law & Regulatory Practice; Developing countries